Artificial Intelligence in Healthcare: Current Applications, Regulatory Frameworks and Future Directions - SYED ZOHAIB,; RAI KHALID FAROOQ, (Pakistan Journal of Medical & Health Sciences, 2025)
Background: AI is solving crucial concerns such as the shortage of workforce specialists and the increasing prevalence of chronic diseases, which is causing a revolution in the delivery of healthcare. AI is revolutionising the delivery of healthcare. Aim: The purpose of this comprehensive analysis is to investigate the uses of artificial intelligence in the disciplines of diagnostics, treatment, and drug discovery. Additionally, this research will analyse the growing regulatory frameworks in important jurisdictions. We synthesise the findings from seventy different studies and policy documents (2016-2024) in order to evaluate the therapeutic efficacy of artificial intelligence (AI), as well as its economic impact and ethical issues. This is done in order to analyse the field of artificial intelligence. Artificial intelligence systems are now capable of matching or surpassing the performance of clinicians in certain diagnostic tasks (for example, achieving a 94% accuracy rate in polyp detection), while simultaneously reducing the amount of time required for drug development by fifty percent. These findings are based on the discovery that we made through our research. However, despite the fact that these issues have been solved, regulatory harmonisation, algorithmic bias mitigation, and governance models continue to provide substantial hurdles. With the assistance of international cooperation and flexible policy making, we present a road map for the responsible adoption of artificial intelligence that strikes a balance between innovation and patient safety. This road map is intended to be implemented in future research. Keywords: Artificial intelligence, healthcare regulation, medical diagnostics, digital therapeutics, ethical AI